2021
DOI: 10.3390/ijms22126490
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Consequences of the Novel Ribosomal Pausing Site in SARS-CoV-2 Spike Glycoprotein RNA

Abstract: The SARS-CoV-2 Spike glycoprotein (S protein) acquired a unique new 4 amino acid -PRRA- insertion sequence at amino acid residues (aa) 681–684 that forms a new furin cleavage site in S protein as well as several new glycosylation sites. We studied various statistical properties of the -PRRA- insertion at the RNA level (CCUCGGCGGGCA). The nucleotide composition and codon usage of this sequence are different from the rest of the SARS-CoV-2 genome. One of such features is two tandem CGG codons, although the CGG c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 66 publications
(94 reference statements)
0
25
0
Order By: Relevance
“…Making the S protein resistant to the enzymatic processing is critical for the rVSV assembly and enhances virus production. The novel ribosomal pausing site, CGGCGG (RR) ( 36 ) was not present in our codon-optimized sequence (AGGAGA) or the R682G mutant (GGGAGA).…”
Section: Discussionmentioning
confidence: 99%
“…Making the S protein resistant to the enzymatic processing is critical for the rVSV assembly and enhances virus production. The novel ribosomal pausing site, CGGCGG (RR) ( 36 ) was not present in our codon-optimized sequence (AGGAGA) or the R682G mutant (GGGAGA).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that artificial deletions in the S1/S2 site produce attenuated virus variants [152]. In fact, an insertion in position 681-684 can alter the viral function [153], suggesting that P681 may be under intense selective pressure.…”
Section: P681 Residuementioning
confidence: 99%
“…The slippery sequence (UUUAAAC) and a downstream hairpin-type pseudoknot help express proteins by causing a deformation of the reading frames ( Bakhshandeh et al., 2021 ). Recently, it has been shown that the -PRRA- insertion sequence thought to be a translational pause site may be involved in the occurrence of stop codons ( Postnikova et al., 2021 ). It has also been demonstrated that codon usage bias, which plays an important role in efficient RNA translation, determines programmed ribosomal frameshifting and ribosome pausing ( Postnikova et al., 2021 ).…”
Section: The Genome Structure General Characteristics Of Sars-cov-2mentioning
confidence: 99%
“…Recently, it has been shown that the -PRRA- insertion sequence thought to be a translational pause site may be involved in the occurrence of stop codons ( Postnikova et al., 2021 ). It has also been demonstrated that codon usage bias, which plays an important role in efficient RNA translation, determines programmed ribosomal frameshifting and ribosome pausing ( Postnikova et al., 2021 ). Insertion of the furin site may be associated with the enhanced infectivity of SARS-CoV-2.…”
Section: The Genome Structure General Characteristics Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation